2001
DOI: 10.1111/j.1096-3642.2001.tb01326.x
|View full text |Cite
|
Sign up to set email alerts
|

Linnaeus's butterflies (Lepidoptera: Papilionoidea and Hesperioidea)

Abstract: The names of all the species of butterflies described by Linnaeus under "Papilio" are researched. Of the 305 names treated, 243 (c. 80%) are currently valid as specific (241) or subspecific (2), 29 are junior synonyms, 14 are invalid (one of these applying t o a fake), and for 13 the identity is unknown or uncertain. Six species of moths misidentified by Linnaeus as butterflies are cited in the study, but details are not included. One hundred and fifty-two lectotypes have been designated, representing about 56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…We have shown that this method is reliable and robust when used to genotype insect specimens collected at least as far back as the early 19th century and possibly earlier. The oldest preserved insect collections still extant are the James Petiver (1665–1718), Hans Sloane (1660–1735) and Joseph Banks (1743–1820) collections at the Natural History Museum, London (Stearns, ; Hawkins, ; Seaward, ), the Carl Linnaeus (1707–1778) collection at the Linnean Society of London (Tanner, ; Honey & Scoble, ), the Kilian Stobaeus (1690–1742) collection at the Biological Museum of Lund University and the Queen Ludovica Ulrica (1720–1782) collection at the Evolution Museum of Uppsala University in Sweden (Kim & Lindroth, ; Honey & Scoble, ). Yet, preserved insect material from the 17th and even most of the 18th century is very scarce (Lalonde & Marcus, ).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that this method is reliable and robust when used to genotype insect specimens collected at least as far back as the early 19th century and possibly earlier. The oldest preserved insect collections still extant are the James Petiver (1665–1718), Hans Sloane (1660–1735) and Joseph Banks (1743–1820) collections at the Natural History Museum, London (Stearns, ; Hawkins, ; Seaward, ), the Carl Linnaeus (1707–1778) collection at the Linnean Society of London (Tanner, ; Honey & Scoble, ), the Kilian Stobaeus (1690–1742) collection at the Biological Museum of Lund University and the Queen Ludovica Ulrica (1720–1782) collection at the Evolution Museum of Uppsala University in Sweden (Kim & Lindroth, ; Honey & Scoble, ). Yet, preserved insect material from the 17th and even most of the 18th century is very scarce (Lalonde & Marcus, ).…”
Section: Discussionmentioning
confidence: 99%
“…There are names available for each of the three entities: meone Stoll, 1780 (type locality: Algeria), aegeria Linnaeus, 1758 (type locality: South Europe and North Africa) and tircis Godart, 1821 (type locality: France). However, using these names is complicated by the fact that the type locality of aegeria is given as 'South Europe and North Africa' and no type material exists (see Honey & Scoble, 2001). Fixing the name to populations in southern Europe would require a neotype, and such an act is beyond the scope of this paper.…”
Section: Discussionmentioning
confidence: 99%
“…In the beginning, Linnaeus named Papilio echion from a written description and a referenced illustration that refer to two unrelated species with similar ventral wing patterns. The nomenclatural identification of Tmolus echion that has been accepted almost universally in the taxonomic literature for over a century does not refer to the bromeliad feeders (Honey & Scoble 2001;Robbins 2004b). The name Thecla basilides does refer to a pineapple-feeding hairstreak, but is a junior synonym of S. megarus (Robbins 2004b).…”
Section: The Tangled History Of "Thecla Basilides"mentioning
confidence: 99%